Contralesional Structural Plasticity in Different Molecular Pathologic Subtypes of Insular Glioma - Huang, Zhenxing; Li, Gen; Li, Zhenye; Sun, Shengjun; Zhang, Yazhuo; Hou, Zonggang; Xie, Jian (Frontiers in Neurology, 2021)
Neuroplasticity may preserve neurologic function in insular glioma, thereby improving prognosis following resection. However, the anatomic and molecular bases of this phenomenon are not known. To address this gap in knowledge, the present study investigated contralesional compensation in different molecular pathologic subtypes of insular glioma by high-resolution 3-dimensional T1-weighted structural magnetic resonance imaging. A total of 52 patients with insular glioma were examined. We compared the gray matter volume (GMV) of the contralesional insula according to histological grade (low-grade glioma, LGG and high-grade glioma, HGG) and molecular pathology status (isocitrate dehydrogenase [IDH] mutation, telomerase reverse transcriptase [TERT] promoter mutation, and 1p19q codeletion) by voxel-based morphometry (VBM). A cluster of 320 voxels in contralesional insula with higher GMV was observed in glioma with IDH mutation as compared to IDH wild type tumors by region of interest-based VBM analysis (family-wise error-corrected at p<0.05). The GMV of the entire contralesional insula was also larger in insular glioma patients with IDH mutation than in patients with wild-type IDH. However, there was no association between histological grade, TERT promoter mutation or 1p19q codeletion and GMV in the contralesional insula. Thus, IDH mutation is associated with greater structural compensation in insular glioma. These findings may be useful for predicting neurocognitive and functional outcomes in patients undergoing resection surgery.